A novel splice site mutation in SMARCAL1 results in aberrant exon definition in a child with schimke immunoosseous dysplasia. (5th May 2015) - Carroll, Clinton; Hunley, Tracy E.; Guo, Yan; Cortez, David
<x xml:space="preserve">Abstract</x> Schimke Immunoosseous Dysplasia (SIOD) is a rare, autosomal recessive disorder of childhood characterized by spondyloepiphyseal dysplasia, focal segmental glomerulosclerosis and renal failure, T‐cell immunodeficiency, and cancer in certain instances. Approximately half of patients with SIOD are reported to have biallelic mutations in SMARCAL1 (SWI/SNF‐related matrix‐associated actin‐dependent regulator of chromatin, subfamily a‐like 1), which encodes a DNA translocase that localizes to sites of DNA replication and repairs damaged replication forks. We present a novel mutation (NM_014140.3:c.2070+2insT) that results in defective SMARCAL1 mRNA splicing in a child with SIOD. This mutation, within the donor site of intron 12, results in the skipping of exon 12, which encodes part of a critical hinge region connecting the two lobes of the ATPase domain. This mutation was not recognized as deleterious by diagnostic SMARCAL1 sequencing, but discovered through next generation sequencing and found to result in absent SMARCAL1 expression in patient‐derived lymphoblasts. The splicing defect caused by this mutation supports the concept of exon definition. Furthermore, it illustrates the need to broaden the search for SMARCAL1 mutations in patients with SIOD lacking coding sequence variants. © 2015 Wiley Periodicals, Inc.